Red at the bone eaudiobook A novel. - Woodson, Jacqueline (Penguin Audio, 2019)
Named one of the Most Anticipated Books of 2019 by LitHub and The Millions. Called one of the Top 10 Literary Fiction titles of Fall by Publishers Weekly. An extraordinary new novel about the influence of history on a contemporary family, from the  New York Times -bestselling and National Book Award-winning author of  Another Brooklyn  and  Brown Girl Dreaming . Two families from different social classes are joined together by an unexpected pregnancy and the child that it produces. Moving forward and backward in time, with the power of poetry and the emotional richness of a narrative ten times its length, Jacqueline Woodson's extraordinary new novel uncovers the role that history and community have played in the experiences, decisions, and relationships of these families, and in the life of this child. As the book opens in 2001, it is the evening of sixteen-year-old Melody's coming of age ceremony in her grandparents' Brooklyn brownstone. Watched lovingly by her relatives and friends, making her entrance to the soundtrack of Prince, she wears a special custom-made dress. But the event is not without poignancy. Sixteen years earlier, that very dress was measured and sewn for a different wearer: Melody's mother, for her own ceremony— a celebration that ultimately never took place. Unfurling the history of Melody's parents and grandparents to show how they all arrived at this moment, Woodson considers not just their ambitions and successes but also the costs, the tolls they've paid for striving to overcome expectations and escape the pull of history. As it explores sexual desire and identity, ambition, gentrification, education, class and status, and the life-altering facts of parenthood,  Red at the Bone  most strikingly looks at the ways in which young people must so often make long-lasting decisions about their lives—even before they have begun to figure out who they are and what they want to be. Read by Jacqueline Woodson, with Quincy Tyler Bernstine ( Sabe ), Peter Francis James ( Po’Boy ), Shayna Small ( Iris ), and Bahni Turpin ( Melody )